Social representations of sales work by catalog: a reading of women and businesses (Emancipação, 2022)
This article aimed to identify the social representation of catalog sales work, based on the review of some YouTube videos of some of the companies that have it as a central business strategy, and interviews conducted with women about their experiences in this activity. The methodology, based on the theory of social representation, was quantitative-qualitative, and used the Iramuteq analysis software, based on the analysis of similarity and the hierarchical classification of the speeches of videos and interviews, to reach conclusions. The results identified that the positions between women and companies regarding the social representations of sales work are materialized in discourses that may seem similar, but that observing them in detail they have important differences, since women see it as a job, while companies they promote it as a way to develop a sole proprietorship.
Keywords: Invisible work. Imaginary. Sales. Social Roles.